(untitled) - Reynolds, Marianne C.; Marianne C. Reynolds (Boston, 1998)
This second book in a 3-volume series of vocabulary texts is devoted to word parts (prefixes, suffixes, and roots) and emphasizes learning vocabulary in context. Designed to serve as a supplement to any developmental reading text or as a stand-alone text in any vocabulary enrichment course, it can also be purchased shrinkwrapped with Book 1 to create a comprehensive vocabulary package. Each chapter provides a variety of exercises and self-tests to enable students to work independently and also offers group activities for those instructors who wish to foster collaborative learning
Keywords: Vocabulary